hey guys, so I'm doing some limit questions, and I'm kind of stuck on one, and it's a even number so I have no solution for it in the book onto how to do it, but anyways this is what I have for this question so far.

Question:

lim (3+h)^{-1}-3^{-1}/ h

h ->0

Ok so this is what I've done so far,

lim 1/(3+h) - 1/3 all divided by h

h ->0

lim 3-(3+h)/3(3+h) all divided by h

h ->0

lim 3-3-h/9+3h * 1/h

h ->0

lim 3-3-1/9+3h (cancelled the h's)

h ->0

Plug in the 0s where the h is -1/ 9+3(0) = -1/9,

Not sure if this is correct or not, and I think I may have made a mistake somewhere, please correct me if so.

Thank you, sorry if the format isn't as good, I think some of you know I'm terrible with that stuff lol.